Synthesis and Antimicrobial Activity of 1-Phenyl/Substituted Phenyl/Benzyl/ Naphthyl-2-Phenyl-4-(3´ -Phenoxy Benzylidene)-Imidazoline-5-ones - Solankee, Anjani; Kapadia, Kishor; Patel, Jayesh; Thakor, Indrajit (Asian Journal of Chemistry, 2010)
2-Phenyl-4-(3´-phenoxy benzylidene)-2-oxazole-5-one react with aromatic/ substituted aronaatic/benzyl/naphthyl amine in presence of pyridine to give 1-phenyl/substituted phenyl/benzyl/naphthyl-2-phenyl-4-(3´-phenoxy benzylidene)-imidazoline-5-ones. The physical and spectral data of the synthesised compounds were determine by elemental and spectral analysis. The synthesised coumpounds were screened for their in vitro antibacterial acitvity.